Peran Itikad Baik Mediasi dalam Proses Penyelesaian Konflik Keluarga - Edi Kamal; Fazzan Fazzan; Azhari Azhari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Family conflict is a common phenomenon that can negatively impact emotional well-being and the stability of relationships between family members. Mediation, as an alternative conflict resolution, offers a constructive approach by involving a neutral third party. The goodwill of the conflicting parties is a crucial factor in the success of the mediation process. This article examines the important role of goodwill in family mediation, including honesty, openness, willingness to listen, respect, focus on solutions, and adherence to agreements. Mediation has been shown to be effective in resolving various types of family conflicts, such as intergenerational conflict, sibling conflict, and marital conflict. The benefits of mediation include maintaining family relationships, tailored solutions, confidentiality, and empowering family members to take control of conflict resolution. The mediator plays a vital role in facilitating the mediation process and creating a conducive environment. The conclusion of this study is that goodwill is the foundation of successful family mediation. When conflicting parties approach mediation in good faith, they can reach solutions that strengthen family relationships and enhance mutual well-being.